Distillation column inherent safety index at preliminary design stage. (December 2018) - Shariff, Azmi Mohd; Athar, Muhammad; Buang, Azizul; Khan, Muhammad Ishaq; Hermansyah, Heri
Abstract: Distillation columns are widely used in many chemical process industries, especially in oil and gas processing. Accidents in the distillation columns have resulted in enormous loss of human lives and assets. Inadequate design of distillation columns is one of the vital reason for the failure, which can be enhanced through inherent safety concept. Therefore, this paper introduces a new indexing method for designing inherently safer distillation columns right from the preliminary design stage. Distillation Column Inherent Safety Index (DCISI) is based on three sub-indices; chemical index, process index and distillation index. These sub-indices are estimated through individual scores by considering various parameters in each category. For the unacceptable score, modification of process conditions is used to enhance safety level of the design. DCISI is estimated for all combination of conditions and lowest DCISI value indicates the inherently safer design of the distillation column.